Developing an ethnomathematics-based digital comic for learning systems of linear equations in two variables to enhance students’ mathematical literacy - Putri Anugrah Ayuning Pratiwi; Annis Deshinta Ayuningtyas; Betty Kusumaningrum; Denik Agustito; Myrat Hayytjanov (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aimed to develop an ethnomathematics-based digital comic on Systems of Linear Equations in Two Variables (SLETV) and to examine its validity, practicality, and potential effectiveness in supporting students’ mathematical literacy. The study employed a Research and Development (R&D) approach using the 4D model, consisting of define, design, develop, and disseminate stages, although the development process was limited to the develop stage. A one-group pretest–posttest design was applied during the field-testing phase without a comparison group. The participants included 10 eighth-grade students and one mathematics teacher in the limited trial, followed by 30 eighth-grade students and one mathematics teacher in the field trial at Mangunan Eksperimental Junior High School. Data were collected through observations, interviews, questionnaires, and mathematical literacy tests. The literacy assessment was designed based on the OECD mathematical literacy processes of formulating, employing, and interpreting mathematics in contextual situations. The developed digital comic integrates Yogyakarta cultural contexts, including batik and local culinary products, into literacy-oriented SLETV learning activities. The validation results indicated a very high level of validity, with scores of 94% from content experts and 86% from media experts. Practicality was supported by positive responses from students (87.86%) and teachers (86%). The field trial results showed an improvement in students’ mathematical literacy, as reflected in an average N-Gain score of 0.58, categorized as moderate, and a statistically significant difference between pretest and posttest scores. These findings suggest that the developed digital comic has the potential to support mathematical literacy development in the tested context and may serve as a valid and practical learning medium for junior high school mathematics learning. This study contributes to mathematics education by demonstrating how local ethnomathematical contexts can be systematically integrated into digital comic media to promote OECD-oriented mathematical literacy in SLETV learning.